In vitro antioxidant and cytotoxic potential of different parts of Tephrosia purpurea - Ramamoorthy Padmapriya; Sankar Ashwini; Ramasamy Raveendran (Wolters Kluwer Medknow Publications, 2017)
The antioxidant and cytotoxic properties of four major parts of methanolic extracts of Tephrosia purpurea including leaves, root, stem and seed were investigated and compared. In vitro antioxidant activity of T. purpurea extracts was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), reducing power assay and antihemolytic assay. In vitro cytotoxic effect of T. purpurea extracts on SW620 colorectal cancer cell line was studied using 3-(4, 5-dimethylthiazolyl -2,5-diphenyl-tetrazolium bromide (MTT) assay. Folin-ciocalteu and aluminium chloride methods were used to determine the total phenolic and flavonoid contents respectively. Among the four extracts studied, leaves extract showed the highest antioxidant activity, DPPH: 186.3 ± 14.0 μg/mL, FRAP: 754.2 ± 50.9 μmol Fe(II)/mg and reducing power activity: 65.7 ± 4.2 μg/mg of quercetin equivalent (QE/mg) and there was no significant difference observed in antihemolytic activity. Leaves extract showed effective cytotoxicity on colorectal cancer cells (IC 50 : 95.73 ± 9.6 μg/mL) and also had the higher total phenolic (90.5 ± 6.7 μg/mg of gallic acid equivalent (GAE/mg) and flavonoid content (21.8 ± 5.4 μg QE/mg). These results suggest higher antioxidant and cytotoxic activities of leaves extract in comparison with other extracts and these activities could be due to the presence of rich phenolic and flavonoid content.